MiR-10a-5p suppresses hepatocellular carcinoma progression and microvascular invasion by targeting TFR1-STAT3-CD24 signaling axis - Zhang, Yupeng; Lai, Di; Wang, Ziyi; Nong, Xiaoyue; Chen, Yingying; Xu, Rulin; Bai, Tao; Zhang, Wei (Frontiers in Oncology, 2026)
BackgroundPreoperative CT features have demonstrated potential in predicting microvascular invasion (MVI) in hepatocellular carcinoma. These CT signs serve as indicators of tumor biological behavior. However, the molecular mechanisms underlying the ability of CT to preoperatively predict MVI remain largely unexplored. This study aims to elucidate the role of miR-10a-5p in HCC progression and investigate its correlation with specific imaging features.MethodsAccording to preoperative CT features, patients were divided into CT-MVI (+) group and CT-MVI (-) group. MiR-10a-5p expression was analyzed in HCC tissues with CT-MVI compared to those without CT-MVI. The functional effects of miR-10a-5p were assessed through in vitro cell viability and apoptosis assays, and in vivo xenograft models. Cell viability was assessed through the CCK8 assay, while flow cytometry was utilized to determine cell apoptosis. The regulatory relationships between miR-10a-5p, CD24, transferrin receptor 1 (TFR1), and STAT3 signaling were explored using western blot, luciferase reporter assays, and rescue experiments.ResultsMiR-10a-5p expression was significantly downregulated in HCC tissues with CT-MVI compared to those without CT-MVI. Overexpression of miR-10a-5p reduced cell viability, promoted apoptosis, and inhibited tumor growth in vivo. MiR-10a-5p directly targeted TFR1, leading to decreased CD24 expression and reduced STAT3 phosphorylation. TFR1 overexpression partially rescued the effects of miR-10a-5p on cell apoptosis and CD24 expression.ConclusionsOur findings reveal miR-10a-5p as a key regulator of HCC progression and MVI, operating through a novel pathway involving TFR1, STAT3, and CD24. This study provides new insights into the molecular mechanisms of CT features and highlights potential therapeutic targets for HCC treatment.